Integration of TPACK in the Implementation of Arabic Language Learning in the Digital Technology-Based Kurikulum Merdeka - Nisa, Ainy Khairun; Annisa, Nur Kholifah; Gunawan, Fahmi (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2025)
A gap analysis of the literature indicates that while research on the implementation of the Merdeka Curriculum is well-documented, its integration with the Technological Pedagogical Content Knowledge (TPACK) framework, particularly in Arabic language learning, remains under-investigated. This qualitative case study aims to analyze the implementation process of the Merdeka Curriculum integrated with TPACK in Arabic language instruction at a Madrasah Aliyah in Southeast Sulawesi. Data were collected through observation, interviews, and document analysis. The findings reveal that TPACK integration is operationalized through three main practices: (1) The application of student-centered learning using digital platforms like Quizizz to stimulate critical and creative thinking through scenario-based tasks, multimedia prompts, instant feedback, and self-paced learning; (2) Adaptive learning tailored to student development stages, characterized by the teacher's ability to balance content, pedagogy, and technology, utilizing WhatsApp for consultation; and (3) Inter-teacher collaboration in developing syllabi, teaching materials, and assessments using WhatsApp Groups and Google Classroom. This study concludes that TPACK integration can be effectively embodied within the Merdeka Curriculum through integrated pedagogical strategies and contextualized use of technology.